Land value tax in the context of sustainable urban development and assessment. Part II ‐ analysis of land valuation techniques: The case of Vilnius - Raslanas, Saulius; Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Zabulėnas, Arūnas Remigijus (International Journal of Strategic Property Management, 2010)
Part Two of this article deals with problems related to land valuation. For that purpose, a site of 6.89 ares located in Švitrigailos Street XX, Vilnius, was selected as the research object and appraised using three approaches: the sales comparison approach, the MAMVA method and the mass valuation approach. Peculiarities of these methods in land valuation were reviewed and the recommendations were provided for land valuation for taxation purposes applicable in a new Model for Lithuanian Real Property Taxation System.First Published Online: 09 Jun 2011